Novel mechanism of arenavirus-induced liver pathology. - Juliane I Beier (PLoS ONE, 2015)
Viral hemorrhagic fevers (VHFs) encompass a group of diseases with cardinal symptoms of fever, hemorrhage, and shock. The liver is a critical mediator of VHF disease pathogenesis and high levels of ALT/AST transaminases in plasma correlate with poor prognosis. In fact, Lassa Fever (LF), the most prevalent VHF in Africa, was initially clinically described as hepatitis. Previous studies in non-human primate (NHP) models also correlated LF pathogenesis with a robust proliferative response in the liver. The purpose of the current study was to gain insight into the mechanism of liver injury and to determine the potential role of proliferation in LF pathogenesis. C57Bl/6J mice were infected with either the pathogenic (for NHPs) strain of lymphocytic choriomeningitis virus (LCMV, the prototypic arenavirus), LCMV-WE, or with the non-pathogenic strain, LCMV-ARM. As expected, LCMV-WE, but not ARM, caused a hepatitis-like infection. LCMV-WE also induced a robust increase in the number of actively cycling hepatocytes. Despite this increase in proliferation, there was no significant difference in liver size between LCMV-WE and LCMV-ARM, suggesting that cell cycle was incomplete. Indeed, cells appeared arrested in the G1 phase and LCMV-WE infection increased the number of hepatocytes that were simultaneously stained for proliferation and apoptosis. LCMV-WE infection also induced expression of a non-conventional virus receptor, AXL-1, from the TAM (TYRO3/AXL/MERTK) family of receptor tyrosine kinases and this expression correlated with proliferation. Taken together, these results shed new light on the mechanism of liver involvement in VHF pathogenesis. Specifically, it is hypothesized that the induction of hepatocyte proliferation contributes to expansion of the infection to parenchymal cells. Elevated levels of plasma transaminases are likely explained, at least in part, by abortive cell cycle arrest induced by the infection. These results may lead to the development of new therapies to prevent VHF progression.